APLIKASI PENENTUAN HARGA SONGKET MENGGUNAKAN METODE EXTREME PROGRAMMING - Anti Susilawati; Khairul Imtihan; Sofiansyah Fadli (Pusat Riset dan Inovasi Nasional, 2022)
Sukarara Village is one of the largest traditional weaving centers in Central Lombok which has several songket motifs or ornaments that have their own motifs, so that many Lombok people and people from outside the city and abroad come to see how to make songket weaving. and sizes that are sold in the market of course with prices also vary. Such as prices (3 million, 2 million 500, 1 million and 500 hundred), as well as motifs such as motifs (keker, stork, kerit, orchid, subahanale and others), as is the case with thread types such as (silk, marcis, gold, etc.) , cotton and rayon) as well as sizes such as (2 m long – 110 cm wide, 110 cm long – 190 cm wide and 60 cm long – 2 m wide). With the problem of determining the price of songket, one alternative solution that can be used is to design a songket pricing application system that can help provide solutions to buyers. The Extreme Programming method itself is the most widely used approach to software development. So in this study it is very suitable to use Xp because the nature of the application made is done quickly through the existing stages such as: planning, designing, coding, and testing. thread.